HUMANISM VALUE OF MAIN CHARACTER IN WAR FOR PLANET OF THE APES MOVIE - Euis Meinawati; Inge Dwiana Haryati; Meiva Eka Sri Sulistyawati; Viviana Lisma Lestari; Syukri Ghozali (Jurnal Metamorfosa, 2020)
This study discusses the humanity values contained in the characters War for Planet of The Apes movie. This analysis uses method of qualitative data. This study uses two kinds of data. Firstly, the primary data is from the literary work itself, War for Planet of the Apes.The secondary data such as theory books, previous studies, and journals. The data analyzed is taken from the player’s remarks in War for Planet of The Apes movie. The theory taken to discuss human values is Hardiman's theory. Hardiman said there are six of humanism values, they are (1) appreciate opinions, (2) cooperation, (3) sacrafice, (4) care about others, (5) helping, and (6) solidarity. The results of this analysis are humanitarian values that arise in the main character in terms of human nature, and how the value of humanity is realized in real life. There are four humanism values that contained in the movie, namely (1) cooperation, (2) care about others, (3) sacrifice, and (4) helping. Penelitian ini membahas tentang nilai kemanusiaan yang terdapat pada karakter dalam film War for Planet of The Apes. Metode yang dilakukan dalam menganalisis adalah kualitatif data. Pertama, data primer adalah War for Planet of The Apes. Dan data kedua seperti buku teori, pelajaran sebelumnya dan jurnal. Data yang dianalisis diambil dari ucapan pemain dalam film War for Planet of The Apes. Teori yang diambil untuk membahas nilai-nilai kemanusiaan adalah teori Hardiman. Hardiman berpendapat bahwa ada enam nilai kemanusiaan, yaitu (1) kebebasan berpendapat,(2) kerjasama, (3) rela berkorban, (4) peduli terhadap sesama, (5) menolong, dan (6) solidaritas. Hasil dari analisis ini adalah nilai-nilai kemanusiaan yang timbul pada karakter utama dalam hal sifat humanisnya, dan bagaimana nilai kemanusiaan ini terealisasikan dalam kehidupan nyata. Nilai kemanusiaan yang terdapat dalam film tersebut ada empat, yaitu (1) kerjasama, (2) peduli terhadap sesama, (3) rela berkorban, dan (4) menolong. Kata Kunci: Film, Karakter Utama, Nilai-Nilai Kemanusiaan